DESIGN THINKING PROCESS IN SME, IS IT STILL POWERFUL IN DEALING WITH THE COVID 19 MARKET TURBULENCE? - Efrata, Tommy C.; Radianto, Wirawan E. D.; Nahar, Faiza Husnayeni (Universitas Brawijaya, Indonesia, 2022)
Studies on SME new product development utilizing the design thinking methodology during the pandemic have received little attention from academics. This study aims to examine how a firm's new product and performance are impacted by the design thinking process. The study was carried out at the height of Covid-19's market dominance. Data was gathered using an online survey of 187 SMEs from diverse industries located throughout Indonesia. Purposeful sampling is conducted to find the chosen companies, particularly those that have altered their business model or added new products. The data is then analyzed and modelled using SEM-PLS to determine how the concepts connect. This study discovered that SMEs can still use the design thinking method to assist them in coping with the effects of the pandemic. It has also been demonstrated that market volatility makes the design thinking method less effective. The study highlights the significance of a firm's absorptive capacity for fostering the design-thinking process. The results of this study demonstrate how design thinking helps a business succeed during a period of significant changes in customer behavior, bridging a knowledge gap. The study's conclusions might help SMEs modify their business practices during and after the pandemic.